Violence in Abyei: Legal Implications of the Sudan-South Sudan Dispute - Yordan Gunawan; Ahmad Zulfiqri A. Lalu (Brawijaya Law Journal, 2024)
Peace and security in the Abyei region are still a tough challenge marked by a historic conflict involving a series of attacks that have caused many casualties. This research focuses on the analysis of dispute cases in South Sudan and also the legal implications of Sudan's dispute with South Sudan in the Abyei region. The materials used in this study include books, journals, and international conventions. This study used the normative legal research method and conducted a literature review approach by studying various reading sources through the internet in accordance with the problem being studied. The research found the legal implications of the conflict in Abyei with human rights violations with implications for the displacement and forced displacement of people in conflict areas. Although to achieve peace in the Abyei region, many countries have been involved as external facilitators, as well as international organizations such as the United Nations, through the establishment of the United Nations Mission in South Sudan (UNMISS).